Dampak Implementasi anda Tangan Elektronik Terhadap Jumlah Akta Kelahiran - Laksono, Haryo; Gultom , Yohanna Magdalena Lidya (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2023)
This study compares the impact of the policy on implementing electronic signatures in the issuance of birth certificates in regencies/cities with low and high means years of schooling parents. Using Indonesian Susenas data from 2010-2021 and DID methods, this study finds that implementing electronic signatures could increase the number of birth certificates of 291 documents. However, by comparing the increase in the number of birth certificates subject to the number of birth certificates and the number of births, this study found that the impact of implementing electronic signatures was relatively low, around 7,02% and 3,73% in increasing the coverage of birth certificate ownership. This study also found economic benefits where each 1 rupiah of costs incurred generates 1,029 rupiahs in benefits. Electronic signatures can solve the difficulty of accessing civil registration services before implementation in regencies/cities with a low mean year of schooling parents but have a relatively low effect on increasing the coverage of birth certificate ownership.